Answer:
-4 and 5
Explanation:
When solving quadratic equations it's important to remember that they have 2 solution. We need to work out the factors, sum and the products to successfully factorise the quadratic and solve it. So,
x² - x - 20 = 0
Sum = -1
Product = -20
So we need two number that sum to -1 and multiply together to make -20
Factors = -5 and 4
x² - 5x + 4x - 20
Factor x² - 5x and 4x -20 separately
x² - 5x = x ( x - 5 )
4x - 20 = 4 ( x - 5 )
So
x ( x - 5 ) + 4 ( x - 5 )
We can see a common factor of ( x - 5 ) and the other bracket would be ( x + 4).
( x - 5 ) ( x + 4 )
But the question asks us for the solution so
x - 5 = 0
x = 5
x + 4 = 0
x = -4